Reaching out to early-career astrobiologists: AbGradE's actions and perspectives. Issue 5 (18th October 2022) - Nauny, Philippe; Cassaro, Alessia; Kopacz, Nina; Noack, Lena; Palabikyan, Hayk; Pinna, Silvana; Price, Alex; Stavrakakis, Hector A.; Taubner, Ruth-Sophie
Abstract: Astrobiology Graduates in Europe (AbGradE, pronounced ab-grad-ee ) is an association of early-career scientists working in fields relevant to astrobiological research. Conceptualized in 2013, it was initially designed as a mini-conference or workshop dedicated to early-career researchers, providing a friendly environment where early-career minds would be able to present their research without being intimidated by the possibility of facing a more traditional audience, composed mainly of senior scientists. Within the last couple of years, AbGradE became the first point of call for European, but also for an increasing number of non-European, early-career astrobiologists. This article aims to present how AbGradE has evolved over the years (in its structure and in its way of organizing events), how it has adapted with the COVID-19 pandemic, and what future developments are considered.